Karakterisasi Asap Cair Hasil Pirolisis Limbah Potongan Rambut Manusia - Lantipo, Yance P. D.; Anom, I. D. K.; Lombok, Johny Z. (General Chemistry Journal, 2024)
Waste piece hair man is difficult decomposes in nature. can pollute environment and influence fertility tana Because No can unraveled by microorganisms with fast. Burning waste piece hair man produce toxic gases and impact for health human and environment. For overcome problem special waste piece hair man so waste hair man shut up as fast Possible melt as fluid oil. For characterization smoke liquid results pyrolysis use Equipment: a set of tools pyrolysis, condenser, bottles 40 liter glass, glass Elemeyer, scales analytical, clamp, pipette, FTIR Spectrophotometer and GC-MS. goal _ For change waste piece hair man become smoke liquid through the pyrolysis process know component compound chemistry analyze FTIR and determine clusters function analyze GC-MS. characteristic chemistry Smoke liquid results pyrolysis waste piece Hair Man can be classified chemical compounds.1. methyl- (CAS) Toluene. 2. Phenol, 4-methyl- 3. 2,4 -imidazolidinedion, 5,5- dimethyl. 4. Sour hexanoate, methyl ester